PERAN EMOTIONAL INTELLIGENCE GURU DALAM PEMBELAJARAN BAHASA ARAB: LITERATURE REVIEW - Abd. Rahman; Yek Abdul Aziz; Adi Fadli (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Arabic language learning is influenced not only by cognitive aspects but also by affective factors, particularly teachers’ emotional intelligence. This study aims to synthesize previous research on the role of teachers’ emotional intelligence in Arabic language learning and its impact on learning processes and outcomes. A literature review method was employed by analyzing scholarly articles published between 2022 and 2026 from databases including Google Scholar, Scopus, Dimensions, Garuda, DOAJ, and Crossref. Data were analyzed using thematic analysis to identify major themes across the selected studies. The findings indicate that teachers’ emotional intelligence consists of four key dimensions: self-awareness, self-regulation, self-motivation, and empathy. Its implementation is reflected in positive communication, the creation of a supportive classroom climate, effective classroom management, and the provision of reinforcement and motivation. Furthermore, teachers’ emotional intelligence contributes positively to students’ learning motivation, self-confidence in speaking Arabic, reduced language anxiety, and improved learning achievement. The study concludes that emotional intelligence is an essential component of Arabic language teachers’ professional competence and plays a significant role in enhancing the effectiveness of Arabic language learning and students’ overall language development.